Determinants of intention to engage in Sustainability Accounting & Reporting (SAR): The perspective of professional accountants - Teddy Ossei Kwakye; Emerald Edem Welbeck; Godfred Matthew Yaw Owusu; Fred Kwasi Anokye (International Journal of Corporate Social Responsibility (JCSR), 2018)
This study examines the perception of professional accountants and the intention to engage in Sustainability Accounting & Reporting (SAR). By relying on the Theory of Planned Behaviour (TPB), the study investigates whether attitudes, subjective norms and perceived behavioural control have any impact on a firm's intention to engage in SAR. A survey method of research was adopted, and a set of questionnaires was developed (based on existing studies) and administered to professional accountants- the respondent group. A total of 86 professional accountants in Ghana voluntarily participated in the study. The partial least square-SEM (PLS-SEM) technique was used to analyse the data obtained. The results from the structural analysis demonstrate that only subjective norm and perceived behavioural control significantly influence a firm's intention to engage in SAR. By implication, the attitude of an accountant towards SAR does not affect the intention to engage in the practice and that the willingness to engage in SAR is primarily determined by resources availability and pressure from major stakeholders.
Keywords: 650; Accountants; Structural equation modelling; Sustainability reporting; Theory of planned behaviour